The perception of smile attractiveness among Saudi population - Mokhtar HA; Abuljadayel LW; Al-Ali RM; Yousef M (Dove Medical Press, 2015)
Hadeel A Mokhtar, Layla W Abuljadayel, Reem M Al-Ali, Mohammed Yousef Department of Operative Dentistry, Faculty of Dentistry, King Abdulaziz University, Jeddah, Saudi Arabia Abstract: Parameters of dental beauty change across time for varying reasons. Thus, an understanding of the factors that help or harm the attractiveness of a smile is an important step in creating attractive smiles. This study aimed to identify factors that affect smile perception and attractiveness among the Saudi population. A cross-sectional study was conducted among the Saudi population. Questionnaires were distributed to 130 dentists and final-year dental students, and to 130 laypersons. The questionnaire contained six smile photographs created by Photoshop® software. There was a statistically significant difference in scale ratings, based on participant background, for the “gummy: smile picture (P-value =0.003), diastema picture (P-value =0.000) and the “Reverse” smile picture (P-value =0.004). As for sex, males significantly underscored the gummy picture (P-value =0.009). Older people accepted the gummy smile less than did younger people, but diastema was considered as one of the variations that spoiled the attractiveness of the smile. “Dental background” participants significantly identified the ideal smile better than the “nondental” group. The perception of diastema as a sign of beauty among Saudi population in the past has definitely changed, according to the results of our study, where diastema and reverse smile received the lowest score in this survey. Keywords: diastema, gummy, reverse